Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.energyfuels.0c02623
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical-Induced Fracturing by Na2S2O8, NaClO, and H2O2 in Marcellus Shale

Abstract: Shale−oxidant reactions can enhance the permeability of organic-rich shale reservoirs through chemical-induced fracturing. Choosing the best oxidant for this purpose is explored in this study. To compare the effects of chemical-induced fracturing with sodium persulfate (Na 2 S 2 O 8 ), sodium hypochlorite (NaClO), and hydrogen peroxide (H 2 O 2 ) on organic-rich shale, Marcellus shale samples were used to conduct spontaneous imbibition experiments in three oxidants' aqueous solutions under no confining pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Organic matter and pyrite are easily oxidized by different acidic or alkaline oxidants such as KMnO 4 , H 2 O 2 , and NaClO. The dissolution capacity of different oxidants in shale was in the order Na 2 S 2 O 8 > NaClO > H 2 O 2 . Strong oxidants such as (NH 4 ) 2 S 2 O 8 and (Na 2 S 2 O 8 ) are widely used in the decomposition of gelling agents in shale hydraulic fracturing, but the main mechanism of interaction between persulfate and shale is calcium sulfate crystals replacing the metasomatism of calcite and dolomite particles .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic matter and pyrite are easily oxidized by different acidic or alkaline oxidants such as KMnO 4 , H 2 O 2 , and NaClO. The dissolution capacity of different oxidants in shale was in the order Na 2 S 2 O 8 > NaClO > H 2 O 2 . Strong oxidants such as (NH 4 ) 2 S 2 O 8 and (Na 2 S 2 O 8 ) are widely used in the decomposition of gelling agents in shale hydraulic fracturing, but the main mechanism of interaction between persulfate and shale is calcium sulfate crystals replacing the metasomatism of calcite and dolomite particles .…”
Section: Methodsmentioning
confidence: 99%
“…The core plug sample (Table 2) used in the nuclear magnetic resonance (NMR) test was drilled from the unweathering outcrop sample, and some rock fragments were obtained during the plug preparations. 18 Strong oxidants such as (NH 4 ) 2 S 2 O 8 and (Na 2 S 2 O 8 ) are widely used in the decomposition of gelling agents in shale hydraulic fracturing, but the main mechanism of interaction between persulfate and shale is calcium sulfate crystals replacing the metasomatism of calcite and dolomite particles. 19 The stimulation of (NH 4 ) 2 S 2 O 8 will produce significant carbonate precipitation and abundant gypsum precipitation, with a limited oxidation effect with organic matter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, chemical reactions are inevitably enhanced after persulfate addition, making the shale–persulfate interaction a critical geochemical process during hydraulic fracturing. There is also research studying potential alterations of the matrix by oxidation of persulfate and evaluating the effects of oxidative dissolution on shale conductivity. Influencing factors such as an oxidant type, concentration, and shale composition have been compared. , Persulfate is preferred because more fractures result from acidification and crystallization of gypsum compared with thermal decomposition by hydrogen peroxide and secondary precipitation with alkaline sodium hypochlorite. ,, …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the fracture frictional stability and frictional strength are correlated with rock properties, and the rock microstructure and components can largely affect the fracture slip behaviors ranging from regular earthquakes to slow slip and creep Collettini et al, 2011;Fang, et al, 2018). Abundant laboratory experiments and numerical simulations are performed to study the impact of chemical alternation on the physic-mechanical properties of various rocks, such as the effect of chemical solutions on the frictional properties of a quartz-rich sandstone (Feucht and Logan, 1990) and rock fracturing (Karfakis and Akram, 1993;Liang and Sheng, 2020), chemically assisted crack and comminution in frictional deformation (Dunning, et al, 1994), evolution of crack permeability in fluid-rock interaction (Sausse et al, 2001), chemical induced micro-fracturing evolution under real-time computerized tomography experiments (Feng et al, 2004), the compaction creep of sands over time in the chemical environment (Brzesowsky et al, 2014), chemically and mechanically mediated influences on the mechanical and transport characteristics of fractured rock using a fracture aperture model (Min et al, 2009). Despite these progresses, the impact of physic-mechanical properties of rock on the fracture slip stability (e.g., the bifurcation near the stability transition) remains poorly understood.…”
Section: Current Studies and Research Gap Of Slip Transitionmentioning
confidence: 99%